"Does short-term variation in fetal heart rate predict fetal acidaemia?" A systematic review and meta-analysis. (16th December 2016) - Kapaya, Habiba; Jacques, Richard; Rahaim, Nadia; Anumba, Dilly
Abstract: Objective : To evaluate the association of short-term variation (STV) of the fetal heart rate in predicting fetal acidaemia at birth. Methods : The search strategy employed searching of electronic databases (MEDLINE, Web of Science, Scopus, and Google Scholar) and reference lists of relevant studies. Data were extracted from studies, adhering strictly to the following criteria: singleton pregnancy at ≥24 weeks' gestation, computerized CTG (index test) and calculation of STV before delivery. The outcome measure was arterial pH assessed in cord blood obtained at birth. Results : Meta-analysis showed moderate accuracy of STV in predicting fetal acidaemia with a sensitivity of 0.57 (95% CI: 0.45–0.68), specificity of 0.81 (95% CI: 0.69–0.89), positive likelihood ratio of 3.14 (95% CI: 2.13–4.63) and negative likelihood ratio of 0.58, (95% CI: 0.46–0.72). However, in intra-uterine growth restricted fetuses, a small improvement in detecting acidaemia was observed; with a sensitivity of 0.63 (95% CI: 0.49–0.75) and negative likelihood ratio of 0.50 (95% CI: 0.31–0.80). Conclusion : STV appears to be a moderate predictor for fetal acidaemia. However, its usefulness as a stand-alone test in predicting acidaemia in clinical setting remains to be determined.